Characteristics of heterosexually-acquired compared to homosexually-acquired HIV and implications for clinical practice: results from the Australian HIV Observational Database. Issue 5 (4th May 2022) - Herbert, S.; Puhr, R.; Petoumenos, K.; Lewis, D. A.; Varma, R.; Couldwell, D. L.; Law, M.; Templeton, D. J.
ABSTRACT: Heterosexuals living with HIV report feeling additional HIV stigma compared to homosexual men, which may affect clinical outcomes. Yet, beyond routinely collected surveillance data, little is known about the characteristics of individuals who acquire HIV heterosexually and clinical outcomes by mode of sexual acquisition have not been directly compared. Using data from the Australian HIV Observational Database, we compared clinical characteristics of those with heterosexually-acquired (Het-HIV) to homosexually-acquired HIV (Hom-HIV) to investigate any differences and their implications for clinical management. 513 Het-HIV and 1467 Hom-HIV patients were included and contributed 3, 127 and 9, 457 person-years of follow-up, respectively. Compared with Hom-HIV, Het-HIV were more often born outside Australia (62.5% vs 39.9%, p <0.001), less likely to have Hepatitis C (4.8% vs 7.8%, p =0.029) and had lower median CD4 counts at diagnosis (292 vs 450 cells/µL, p <0.001) and cART initiation (270 vs 340 cells/µL, p <0.001). Despite these lower CD4 counts, there were no significant differences between groups for time to the major clinical endpoints of cART initiation, viral suppression, virological failure or all-cause mortality. Het-HIV had a lower risk of loss-to-follow-up than Hom-HIV (aHR 0.78; 95% CI 0.64-0.95). Further studies examining factors associated with, and interventions to inform retention in care are required.